2022
DOI: 10.1186/s12951-022-01410-z
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-sensing catalase-mimicking nanozymes alleviate acute kidney injury via reversing local oxidative stress

Abstract: Background The reactive oxygen species (ROS) and inflammation, a critical contributor to tissue damage, is well-known to be associated with various disease. The kidney is susceptible to hypoxia and vulnerable to ROS. Thus, the vicious cycle between oxidative stress and renal hypoxia critically contributes to the progression of chronic kidney disease and finally, end-stage renal disease. Thus, delivering therapeutic agents to the ROS-rich inflammation site and releasing the therapeutic agents is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
(41 reference statements)
0
30
0
Order By: Relevance
“…Recently, Choi et al developed nanomicelles able to sense ROS and loaded them with catalase-mimicking 1-dodecanethiol stabilized Mn 3 O 4 . Ultimately, the authors noted that inflammation and apoptosis were attenuated in the renal ischemia/reperfusion injury mouse model [ 170 ].…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
“…Recently, Choi et al developed nanomicelles able to sense ROS and loaded them with catalase-mimicking 1-dodecanethiol stabilized Mn 3 O 4 . Ultimately, the authors noted that inflammation and apoptosis were attenuated in the renal ischemia/reperfusion injury mouse model [ 170 ].…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
“…1-Dodecanethiol-stabilized hydrophobic Mn 3 O 4 nanoparticles were prepared as previously described [11].…”
Section: Synthesis Of Manganese Oxide Nanoparticles and Lipo-mgnsmentioning
confidence: 99%
“…MGN has the advantages that it has over other manganese oxide types, such as MnO, MnO 2 and Mn 2 O 3 , for generating more molecular oxygen. Mn 3 O 4 has a higher ROS-scavenging ability owing to the double oxidation states of Mn3 + and Mn2+, which can lead to the conversion of ROS (˙O2-& ˙OH) to molecular oxygen released in in ammation [11,12]. There are a few reports about Mn 3 O 4 nanoparticles (MGNs) for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Catalasemimicking 1-dodecanethiol stabilized Mn 3 O 4 (dMn 3 O 4 ) NPs entrapped with ROS-sensitive NPs degrade H 2 O 2 as well as suppress TNF-α and IL-6 cytokine secretions, thereby attenuating inflammation in the acute kidney injury mouse model. 47 Previously, we reported a peroxidase-mimicking nanoassembly for anti-inflammation in lipopolysaccharide (LPS)-induced endotoxemia and revealed that the hydrogen peroxide scavenging in LPS-induced macrophages led to reduction in the expression of proinflammatory proteins and cytokines, such as iNOS, Nf-κb, TNFα, and IL-6, thereby preventing aggressive inflammatory responses that cause cognitive damage. 50 Interestingly, our study revealed that reducing intracellular H 2 O 2 levels affected HIF1α, which is considered as the direct activator of the Nf-κb pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatible catalytic NPs, such as manganese dioxide (MnO 2 ), cerium NPs, , and Prussian blue NPs, have the ability to decompose peroxidase and produce oxygen molecules under H 2 O 2 -rich hypoxic environments. Catalase-mimicking 1-dodecanethiol stabilized Mn 3 O 4 (dMn 3 O 4 ) NPs entrapped with ROS-sensitive NPs degrade H 2 O 2 as well as suppress TNF-α and IL-6 cytokine secretions, thereby attenuating inflammation in the acute kidney injury mouse model .…”
Section: Introductionmentioning
confidence: 99%